2022
DOI: 10.2147/ibpc.s361789
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Its Associated Factors Among Long-Distance Truck Drivers in Ethiopia

Abstract: Introduction Hypertension is rising globally and is one of the leading causes of cardiovascular disease. It affects people of different groups; however, owing to a rise in a sedentary lifestyle it is more prevalent among long-distance truck drivers. However, the prevalence of hypertension and its associated factors among truck drivers in Ethiopia is not known. Therefore, this study aimed to determine the prevalence of hypertension and its associated factors among long-distance truck drivers in Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…The mean age of the participants was 39.71 ± 11.07 smoking, and tobacco consumption, as well as the existence of comorbidities like overweight and obesity, may be associated with increased prevalence of HTN. 6,18,19 All 600 participants were male, consistent with other studies. 7,13 Most of the participants had a high school education (54.50%).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The mean age of the participants was 39.71 ± 11.07 smoking, and tobacco consumption, as well as the existence of comorbidities like overweight and obesity, may be associated with increased prevalence of HTN. 6,18,19 All 600 participants were male, consistent with other studies. 7,13 Most of the participants had a high school education (54.50%).…”
Section: Resultssupporting
confidence: 85%
“…23 Around 47% of the participants were hypertensive (including previously known cases) consistent with studies done among ARDs and professional drivers. 13,19,21,24 In general, ARDs have higher levels of HTN, overweight, and obesity than the general population. This can be explained by their sedentary work pattern, long hours of inactivity, constant mental stress, and a higher level of tobacco use all of which are known to be risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…Due to stimulation from the nervous system, the increasing heart rate causes hypertension by increasing the blood pressure on the inner walls of the arteries. A study found that drivers of long-distance trucks with a BMI of 30 kg/m² or higher are more likely to suffer from hypertension [26].…”
Section: Resultsmentioning
confidence: 99%